The gleaner song selected poems - Song, Lin 1958- (Giramondo Publishing Company, 2021)
"Song Lin is one of China's most innovative poets. When the Tiananmen protest exploded in Beijing in June 1989, Song led student demonstrations in Shanghai and was imprisoned for almost a year. He left China soon afterwards. This selection of poems, made by the translator Dong Li and the poet himself, spans four decades of poetic exploration, with a focus on poems written during the poet's long stay in France, Singapore, Argentina, and more recently, his return to China. As a result of his wanderings, Song Lin may be thought of as an international poet, open to an unusual extent to influences - though informed by the classics and a thorough study of the Chinese language, his poetry weaves through American, French, and Latin-American traditions. His influences are the modernists, the surrealists, the romantics, the deep imagists and the objectivists--but what distinguishes Song is his ability to absorb them all, and make them his own." -- Back cover
Keywords: Chinese poetry / 21st century; Chinese poetry / Translations into English; Poésie chinoise / 21e siècle; Chinese poetry; 2000-2099; Poetry; poetry; Translations; Poésie